2021
DOI: 10.3389/fneur.2021.627999
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telerehabilitation on Motor Impairments, Non-motor Symptoms and Compliance in Patients With Parkinson's Disease: A Systematic Review

Abstract: Introduction: Parkinson's disease (PD) is a chronic neurodegenerative disease involving a progressive alteration of the motor and non-motor function. PD influences the patient's daily living and reduces participation and quality of life in all phases of the disease. Early physical exercise can mitigate the effects of symptoms but access to specialist care is difficult. With current technological progress, telemedicine, and telerehabilitation is now a viable option for managing patients, although few studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 91 publications
(153 reference statements)
4
27
0
2
Order By: Relevance
“…However, our data indicate that although technical options were accessible in most PwP (even those with p-LTC, who additionally might not only need technical options but also care staff support to use the technology), acceptance and use of this technique was rather low in both groups. Although telemedicine approaches have been shown to be effective [ 60 , 61 ] and are widely recommended for PwP [ 16 , 32 , 62 ], even by the International Parkinson and Movement Disorder Society [ 1 ], our findings are congruent with previous studies documenting that even high levels of satisfaction with telemedicine did not translate into a sustained interest or use of this health care approach [ 2 , 12 ]. Extensive promotion of remote or virtual care modes that have been found to be as effective as in-person communication [ 63 ] or alternative offerings (e.g., conducting more house calls by medical and/or therapeutical staff, cross-sectoral approaches with PD nurse specialists as in other countries that are only rarely deployed in Germany so far [ 64 ]) should be focused on in the future.…”
Section: Discussionsupporting
confidence: 87%
“…However, our data indicate that although technical options were accessible in most PwP (even those with p-LTC, who additionally might not only need technical options but also care staff support to use the technology), acceptance and use of this technique was rather low in both groups. Although telemedicine approaches have been shown to be effective [ 60 , 61 ] and are widely recommended for PwP [ 16 , 32 , 62 ], even by the International Parkinson and Movement Disorder Society [ 1 ], our findings are congruent with previous studies documenting that even high levels of satisfaction with telemedicine did not translate into a sustained interest or use of this health care approach [ 2 , 12 ]. Extensive promotion of remote or virtual care modes that have been found to be as effective as in-person communication [ 63 ] or alternative offerings (e.g., conducting more house calls by medical and/or therapeutical staff, cross-sectoral approaches with PD nurse specialists as in other countries that are only rarely deployed in Germany so far [ 64 ]) should be focused on in the future.…”
Section: Discussionsupporting
confidence: 87%
“…The a priori criterion of no falls was matched in our cohort, indicating the high safety of our telerehabilitation program in mild-to-moderate PD patients. Moreover, there was no report of any other AE, in line with the results of previous studies underlying the safety of remote rehabilitation in PD patients ( 33 ). Dropout rate and adherence to the program were considered as measures of feasibility.…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, the efficacy of physiotherapy on motor symptoms is widely demonstrated ( 7 ). Moreover, preliminary studies showed efficacy of non-conventional remote administered rehabilitation strategies, including dance or virtual reality training, on motor and non-motor outcomes in PD patients ( 33 ). Our study confirms this extended knowledge to the efficacy of remote administered physiotherapy program on motor symptoms of PD, as measured by the MDS-UPDRS-III score.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicated a high level of satisfaction with this form, its high efficiency, and cost-effectiveness. Overall, it was mostly well received [ 6 , 7 , 8 , 44 ]. Therefore, we expected more responses to the online questionnaire, given that no contact required, possibility of completing the questionnaire at any time of the day existed and a reward of a set of exercises was offered.…”
Section: Discussionmentioning
confidence: 99%
“…Access to physicians and physiotherapists was restricted. In response to the situation, the role of telemedicine (used in general to diagnose, consult and heal, also in the meaning of telerehabilitation) increased [ 5 , 6 , 7 ] and its effectiveness was confirmed even before the pandemic [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%